0196 Mental health inequalities by informal employment and gender in Central America. (23rd June 2014) - López-Ruiz, María; Martínez, José M; Benavides, Fernando G; Puig-Barrachina, Vanessa; Rojas, Marianela; Artazcoz, Lucía
Abstract : Objectives: To analyse the relationship between mental health and non-agricultural informal employment in Central America; and to examine whether patterns of association differ by gender Method: Cross-sectional study of 8904 non-agricultural workers (48% women) based on the I Central American Survey of Working Conditions and Health of 2011. Employment profiles were created combining formal and informal characteristics: labour relationship (permanent employees, temporary employees, self-employed, employers), social security coverage (yes, no), type of contract for employees (written, oral or no contract), company size for employers (≤5, >5 workers). Using logistic regression models, odds ratios (OR) of poor mental health (measured by GHQ12 questionnaire) and 95% confidence intervals (95% CI) were calculated by sex, adjusting for country and age, with employment profiles as independent variable. The reference group was permanent employees covered by social security with a written contract. Results: Around 37% of women and 34% of men reported poor mental health. In both sexes all profiles without social security coverage were associated with poor mental health except for permanent employees. Temporary employees covered by social security were associated with poor mental health if they have oral or no contract for women and men. Covered permanent employees with oral or no contract among women (OR: 1.70, 95% CI:1.12–2.59) and covered self-employed among men (OR: 1.59, 95% CI:1.03–2.46) were associated with poor mental health. Conclusions: In Central America health inequalities by employment profiles exist, principally for not being covered by social security, or having an oral or no contract for employees (main characteristics of informal employment). Few gender inequalities have been found.